RELATIONSHIP OF HEALTH SERVICE QUALITY WITH SATISFACTION OUTSTANDING PATIENTS AT LAMPASEH CENTER BANDA CITY ACEH IN 202 - Nisa, Khairun; Putri Arisca Sari; Eddy Azwar; Agustina; Maidar (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Some Complaints felt by patients are about inadequate health facilities (Tangible), lack of reliability of examining officers (Reliability), less responsive officers (responsiveness), lack of empathy of officers in the registration section, complicated procedures, Long waiting time and providing information that is difficult to understand: n Use descriptive-analytic and cross-sectional design. Data collection was carried out by interviews using a questionnaire. The population in this study were all patients who visited the Lampaseh Health Care Center in Banda Aceh City. The number of outpatient samples is 99, determined by the purposive sampling technique. The data collected were analyzed by univariate and bivariate analysis. This data collection was carried out from 25 to 31 January 2022. Data were analyzed using the chi-square at the 95% confidence level (ρ < 0.05). The results showed that there was a significant relationship between physical evidence and patient satisfaction (p = 0.000) between responsiveness (p = 0.000) in addition, there was also no significant relationship between reliability (p = 0.0478), empathy (p = 0.113) and assurance and patient satisfaction (p = 0.076). Based on the findings, it is recommended that the health center management improve physical evidence and responsiveness to improve patient satisfaction and maintain reliability, empathy, and assurance.